2014
DOI: 10.1021/cg501567s
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Shape-Dependent Luminescent Behavior of Dye Aggregates: Bent versus Linear Benzocoumarins

Abstract: Aggregation patterns of dye molecules can govern their photophysical properties in the solid state. The linear and bent shaped dipolar benzocoumarins showed contrasting luminescence behavior in solution and in the solid state. Single crystal structures of both compounds showed π-stacking patterns with eclipsing but opposite dipole moments when viewed orthogonal to the stacking plane. Although the bent molecules are stacked in parallel in the solid state, they behave as independent molecules owing to the unfavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…Understanding the structure-property relationship is very important to guide the design of correct molecules for their providential applications1617181920212223. Artful molecular design through varying molecular backbone substituent groups and effective π-conjugation lengths or impacting the intra/intermolecular interactions to achieve high emission in the solid state is the most common method2425262728.…”
mentioning
confidence: 99%
“…Understanding the structure-property relationship is very important to guide the design of correct molecules for their providential applications1617181920212223. Artful molecular design through varying molecular backbone substituent groups and effective π-conjugation lengths or impacting the intra/intermolecular interactions to achieve high emission in the solid state is the most common method2425262728.…”
mentioning
confidence: 99%
“…Effort has been put forward to tune the molecular packing through structural modification and thereby influence the solid state fluorescence output. [23][24][25][26][27][28][29][30][31][32][33][34][35] In this regard, small organic derivatives with olefin, acetylene, phenylenevinylene and phenyleneethynylene spacers have found current interest. 19,24,[36][37][38][39][40] Davis et al reported the solid state fluorescence of alkoxy-cyano substituted diphenylbutadiene derivatives.…”
mentioning
confidence: 99%
“…In general,a lteration of the molecular structure and its packing modes in the crystal under external stimuli could affect the emission colour and intensity. [24] The solidP Ls pectra of compounds TPEB, TPEF and TPEN were red shifteda nd accompanied by intensity increasing after grinding, whereas for TPECN,t he peak was red shifted and the intensity was just slightly reduceda fter grinding. Compound TPEB exhibited a F F of 12.28 %w ith ap eak at 477 nm.…”
Section: Mechanofluorochromic Luminescence (Mfc)mentioning
confidence: 92%